2016
DOI: 10.1111/ijpo.12186
|View full text |Cite
|
Sign up to set email alerts
|

Interrelationships of child appetite, weight and snacking among Hispanic preschoolers

Abstract: SummaryBackgroundSnacking among US preschoolers has increased in recent decades, raising questions about whether snacking contributes to dietary excess.ObjectivesThis research aimed to characterize snacking contributions to dietary excess and to evaluate associations with appetite and weight among preschool‐aged children.MethodsThis study is a cross‐sectional, observational study of 187 Hispanic low‐income preschoolers. Three 24‐h dietary recalls were used to assess snacking frequency and parameters of dietary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 22 publications
1
12
1
Order By: Relevance
“…In contrast to the lack of a portion size effect on vegetable intake, children consumed a greater proportion of the typically preferred energy-dense foods (46), particularly snacks. Snacking is a concern because approximately one-third of children's diets comes from snacks, which tend to be energy-dense and contribute to excess energy intakes (47)(48)(49), as they did in the current study. Caregivers need guidance on how to increase both the proportion and palatability of vegetables relative to the more energy-dense components served at meals in order to moderate energy intake (17,50).…”
Section: Discussionsupporting
confidence: 55%
“…In contrast to the lack of a portion size effect on vegetable intake, children consumed a greater proportion of the typically preferred energy-dense foods (46), particularly snacks. Snacking is a concern because approximately one-third of children's diets comes from snacks, which tend to be energy-dense and contribute to excess energy intakes (47)(48)(49), as they did in the current study. Caregivers need guidance on how to increase both the proportion and palatability of vegetables relative to the more energy-dense components served at meals in order to moderate energy intake (17,50).…”
Section: Discussionsupporting
confidence: 55%
“…For instance, an observational study of 5‐ to 6‐year‐old non‐Hispanic Black children ( n = 100) found that those reported by their parents to have lower satiety responsiveness showed greater increases in energy intake across meals at which food portion sizes were systematically increased . Similarly, a study of 187 low‐income Hispanic preschoolers revealed that greater enjoyment of food was associated with more frequent snacking and greater daily energy intake from snacks among children with OW/OB, whereas the opposite was true of children with normal weight . Clearly, experimental and longitudinal designs are required to evaluate temporality and causality in associations of snacking with child appetite and weight outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has also found that the presence of transient stressors (e.g., conflict between parent and child, or having too much work to do) have been associated with an increase in parent engagement in restrictive parent feeding practices ( Berge et al, 2018 ). Given the increased role mothers had in providing snacks to their children during the COVID-19 pandemic (e.g., children at home instead of being provided snacks at daycare), that snacks are often provided when parents need to manage child behavior (e.g., keeping children quiet) ( Blaine et al, 2015 ; Fisher et al, 2015 ), and the important role of snacking in children's daily caloric intake ( Loth et al, 2020 ; Rudy et al, 2018 ), understanding more about how parents navigated child snacking during the COVID-19 pandemic is important.…”
Section: Discussionmentioning
confidence: 99%